Student Psychosocial Adjustment Profiles: A Cluster-Based Analysis - Romera Leme, Vanessa Barbosa (2024)
The end of the middle school is characterized by interpersonal and academic challenges, in addition to high levels of school dropout and failure. However, there are few studies that aim to investigate this period of the educational trajectory, in order to identify personal and contextual resources. Thus, this study aimed to analyze psychosocial adjustment profiles of students, considering risk factors (exposure to violence and daily discrimination), protection (social support and school climate) and adjustment indicator (life satisfaction). 709 students who attended the 7th, 8th and 9th grade of public schools participated. Through cluster analysis, profiles were identified: resilient, with high values of risk indicators with good adjustment; vulnerable, with high-risk indices and low adjustment. It is concluded that investing in the reduction of risk factors and enhancement of protective factors, through preventive programs, is essential for the development.